Seasonal and age dynamics of passalurosis invasion of rabbits and pathological and histological changes in this nematodosis - Mikhailo Prus; Yulia Duda; Lyudmila Koreyba; Borys Borisevich; Victoria Lisova (Наукові горизонти, 2023)
The most common nematode in rabbits is passalurosis, and climate change in Ukraine in recent decades has altered the epizootic manifestation of this parasitosis, which predetermines the relevance of this study. Therefore, the purpose of this paper was to establish the epizootic situation regarding the passalurosis invasion and to investigate the pathological and histological changes in both the large and small intestines of rabbits with a high degree of damage by Passalurus ambiguus. The study used the McMaster method, the improved method of incomplete helminthological dissection according to K.I. Scriabin Private households in the Polissia zone of Ukraine were found to be the most vulnerable in terms of passalurosis infestation, where 37.70-41.67% of sick rabbits were registered. In the seasonal aspect, the highest infection of animals was found in winter (invasion extensiveness (IE) was 35.27%), with a peak in January (IE = 35.29%), the lowest – in summer (IE = 25.79%). Rabbits aged 1 to 2 years had the highest incidence of the pathogen Passalurus ambiguus (82.76%). It was found that with a high degree of damage (invasion intensiveness (II) – 2446.67 ± 422.11 eggs in 1 g of faeces) rabbits with passalurosis had catarrhal and catarrhal-haemorrhagic inflammation, swelling of the mucous membrane of the intestines with dotted or striped haemorrhages. The destruction of the villi of the mucous membrane of the small, caecum, and colon, crypt cells and infiltration by lymphocytes and monocytes, severe swelling of the submucosal base and muscle membrane, and a state of granular dystrophy of all smooth muscle cells of the muscle membrane were established. The detection of seasonal, age-related, and pathological-histological changes in rabbits with passalurosis will allow controlling the degree of infection of animals and promptly taking effective countermeasures, which predetermines the practical value of this study